PENGGUNAAN MODEL GRAVITAS HUFF UNTUK MENGESTIMASI NIAT BERKUNJUNG KE PUSAT PERBELANJAAN - Angga Putra Pratama Siregar; Dina Octaviani (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2022)
The Huff's Gravity Model is known for its function as a determinant of location that relies on the attractiveness of the location resulting from a comparison between the attributes of that location with the obstacles that must be traversed to reach that location. The attractiveness of a location is assessed from the attributes possessed by that location, while the obstacles that must be passed are the distance and the time taken by someone to reach a certain location. This study uses the Huff's Gravity Model to estimate attractiveness, intention, and frequency of visits to shopping centers by using two types of data on aspects of servants, namely actual (objective) data and perceived data (subjective). Furthermore, the results of the study were analyzed using the principle of equivalence reliability to see results between actual data and perceived data, and applycriteria on-related validity to see the results between the calculation of the Huff's Gravity Modelwith measurements of attractiveness, intention to visit again, and frequency of visits to shoppingcenters